New Straits Times, 12 Disember 2007 - Chandra Muzaffar Dr (The New Straits Times Press (M) Bhd, 2007)
No single episode in Malaysian society in recent years has had such a negative impact upon Indo-Malay ties as the actions and allegations of the Hindu Rights Action Force (Hindraf). Its reckless, scurrilous allegations have hurt and angered a lot of Malaysians in all walks of life